The Role of Teachers in Internalizing the Values of Local Wisdom in Madrasah Ibtidaiyah - Nuryana Nuryana; Dede Cahyati Sahrir (UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractThe roles of the teacher in internalizing the values of local wisdom can be seen from the extent of the efforts made by the teacher in developing the values of local wisdom in the learning process. This study aims to describe the roles of teachers and the factors that influence them in internalizing the values of the local wisdom of Cirebon in learning at the Madrasah Ibtidaiyah (Islamic elementary school). A qualitative descriptive study with an ethnographic approach was combined with a quantitative descriptive survey method in this research. Questionnaires, observation, and interviews were utilized to collect data for this study. The findings revealed that instructors' roles in instilling local wisdom values in Islamic elementary school children in Cirebon City had not been fully utilized in the classroom. This can be seen in how the abilities and competencies of teachers who are considered still inadequate to be able to internalize the values of local wisdom in madrasah learning. Local wisdom has so far only been used in the classroom to invite students to tour historical sites, make traditional arts an extracurricular activity, and convey stories about Cirebon's history. Government regulations stating that local wisdom is crucial to its survival and preservation are examples of supporting elements. Teachers, family support, curriculum load, and the cost of visiting cultural sites were discovered to be the most constraining factors.Keywords: teachersâ€™ roles; local wisdom; cirebon city; madrasa.Â AbstrakPeran guru dalam menginternalisasikan nilai-nilai kearifan lokal dapat dilihat dari sejauh mana upaya yang dilakukan guru dalam mengembangkan nilai-nilai kearifan lokal dalam proses pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan peran guru dan faktor yang mempengaruhinya dalam menginternalisasikan nilai-nilai kearifan lokal Cirebon dalam pembelajaran di Madrasah Ibtidaiyah. Penelitian ini menggunakan penelitian deskriptif kualitatif pendekatan etnografi dikolaborasikan dengan deskriptif kuantitatif metode survei. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah angket, observasi dan wawancara. Hasil penelitian menunjukkan bahwa peran guru dalam menginternalisasikan nilai-nilai kearifan lokal kepada siswa Madrasah Ibtidaiyah di Kota Cirebon belum maksimal diterapkan dalam pembelajaran. Hal tersebut terlihat pada bagaimana kemampuan dan kompetensi guru yang dinilai masih belum mumpuni untuk dapat menginternalisasikan nilai-nilai kearifan lokal pada pembelajaran di madrasah ibtidaiyah. Selama ini penerapan kearifan lokal dalam pembelajaran hanya sebatas mengajak siswa kunjungan ke tempat bersejarah, menjadikan kesenian tradisional sebagai salah satu ekstrakulikuler dan bercerita mengenai sejarah cirebon saat pembelajaran. Faktor yang mendukung diantaranya adanya kebijakan pemerintah yang menyatakan bahwa kearifan lokal penting untuk dijaga eksisitensi dan kelestariannya. Adapun faktor yang menghambat ditemukan berasal dari guru, dukungan orangtua, beban kurikulum dan juga biaya kunjungan situs budaya.Kata kunci: peran guru; kearifan lokal; Cirebon; madrasah.